Incidence of childhood Type 1 diabetes mellitus in Crete. Issue 9 (2nd June 2018) - Mamoulakis, D.; Vrouvaki, F.; Louvari, V.; Galanakis, E.
Abstract: Aim: To investigate the epidemiology of childhood Type 1 diabetes mellitus in Crete over the last 25 years and to evaluate incidence trends over time. Methods: The study included all children aged 0–14 years who live in Crete and were diagnosed during the 25‐year period from 1 January 1992 to 31 December 2016. Results: A total of 271 children were diagnosed with Type 1 diabetes during the 25‐year period: 148 boys and 123 girls (boy:girl ratio 1.2). The median (interquartile range) age at diagnosis was 8.3 (5.0–12.0) years for boys and 8.0 (5.3–11.3) years for girls. The standardized annual incidence rate was 10.5 per 100 000 children (95% CI 9.2 to 11.8). Incidence rates were higher in children aged 5–9 years. During the 25‐year study period an average 4.4% annual increase in incidence was documented and was most prominent in the age group 5–14 years. Incidence seemed to remain relatively stable for the age group 0–4 years in the last decade. No seasonality of the clinical onset of Type 1 diabetes was observed. Conclusions: The recent increase in Type 1 diabetes incidence places Crete among regions with high incidence as per the World Health Organization DiaMond project classification. The rising trends in incidence confirmed by this study are in accordance with the reported global trends in Type 1 diabetes incidence. What's new?: Childhood‐onset Type 1 diabetes mellitus seems to be increasing in Crete, an area with very low rates in the past, but recent reports on incidence rates are lacking. Incidence rates now place Crete among regions with a high incidence of Type 1 diabetes. The average annual incidence increase of 4.4% during the 25‐year period studied is considerable and in accordance with global trends in Type 1 diabetes incidence. Incidence rates among the 0–4 years age group have remained relatively stable in the last decade.